POOR WASTE DISPOSAL AND EFFECT ON HEALTH- A REVIEW - Devaraj, Navin Kumar (International Journal of Public Health Science (IJPHS), 2020)
AbstractAs human population grows, so does the generation of waste including faeces, urine and rubbish consisting of plastics, heavy metals and glass among others. Improper waste management has lead to a multitude of physical, psychological and social issues which has direct effect on health of the population which is the main driver of the nation?s economy.Despite efforts by the government to advice consumers on proper rubbish dumping, sadly this tends to falls on deaf ears many a time. Even concerted enforcement has not deterred these so-called rubbish dumpers from carrying out their socially unacceptable behaviours.What is hope is that along with becoming a developed country in term economy driven investments and high income generation by the population, is that it is also important to take care of the environment which serve as a mother to all of us to nurture and nourish us, its? children till the end of civilization or doomsday.